A historical review and approach to a synthetic definition of the concept “Ideology” - Chavarría-Mora, Elías (2025)
What is the evolution of the concept «ideology» in social theory, and is it possible to develop a definition that synthetizes its different aspects? In this essay I review the main conceptualizations of ideology, first from a social theory and western Marxism angle, followed by definitions from sociology and political science, with the objective of building a synthetic definition applicable to empirical work, as well as which are the dimension in which ideologies are situated using the concepts of political values and attitudes taken from the political culture and psychology literature to identify an economic and a social dimension.